E-Marketplace dengan Metode Upselling Study Kasus Toko Bento Sport Berbasis Web - Fajar Diski Saputro; Dwi Tjahjo Seabtian (Journal of Computer System and Informatics (JoSYC), 2021)
Online store or E-commerce is an online business that is growing rapidly at this time. Shoppers can save time and effort by shopping online through e-commerce. With the help of e-commerce, sales are not limited by place and are managed globally. in this topic, BENTO SPORT is a shop that specializes in sports equipment and supplies. In sales, many buyers have difficulty buying products at the BENTO SPORT Shop. From these questions, an online website-based sales application solution was made. With an online sales application, buyers do not have to come back and are not limited by place and time